Flowering phenology in a Eucalyptus loxophleba seed orchard, heritability and genetic correlation with biomass production and cineole: breeding strategy implications - Spencer, Beren; Mazanec, Richard; Abadi, Amir; Gibberd, Mark; Zerihun, Ayalsew (Nature Publishing Group, 2020)
Reproductive synchronicity within a seed orchard facilitates gene exchange and reduces self-fertilisation. Here we assessed key flowering traits, biomass and foliar 1,8-cineole concentrations of Eucalyptus loxophleba (subsp. lissophloia and gratiae) in an open-pollinated seed orchard. Monthly flowering observations were made on 1142 trees from 60 families and nine provenances across 2 years. The percentage of trees flowering in both years was similar at 87%. There were differences between provenances and families within provenances for flowering traits, biomass and 1,8-cineole and interactions between provenances and year for flowering traits. Heritability of start and end flowering, and 1,8-cineole were high to moderate (h^2 = 0.75–0.45) and duration of flowering, propensity to flower and biomass estimates were moderate to low (h^2 = 0.31–0.10). Genetic and phenotypic correlations between flowering traits were high (rg = 0.96–0.63 and rp = 0.93–0.34) except between duration and end of flowering. The correlations were weaker between flowering traits and biomass or 1,8-cineole. ‘Dual flowering’, when trees underwent two reproductive cycles in a year, was responsible for out-of-phase flowering and those with low biomass and 1,8-cineole concentration should be removed from the breeding programme to hasten selection for desirable traits.